JETFIGHTER DOWN! PREDICTING OPINIONS WITH TWITTER AND THE ROLE OF SOCIAL MEDIA IN TURKEY WITHIN CONTEXT OF ATTRIBUTE AGENDA-SETTING THEORY. - SÜTCÜ, Cem Sefa; AYTEKIN, Çiğdem; KARA, Tolga; AKYAZI, Erhan; DILMEN, Necmi Emel; DEĞERLİ, Başak (Journal of International Social Research / Uluslararası Sosyal Araştırmalar Dergisi, 2014)
Newspapers have important role of agenda setting. They have the unique power and opportunity to inform. However, the way to gather, disseminate and follow repercussions of their news is changing. Newsmedia is affected by social media. This change should be carefully analyzed using opinion mining methods on social media like Twitter, where political deliberations are heavily made. We investigated contents of news about a jetfighter incident in 2012 between Turkey and Syria from nine national newspapers and compared them with over 100,000 messages containing reference to the incident from more than 34.000 people on Twitter to find whether messages on Twitter mirror the opinions in newspapers. Using content analysis and semi-supervised opinion mining method, our results show that agendas of newspapers and Twitter users widely differ on the incident, indicating a possible agenda mismatch.